THE EFFECT OF TALKING STICK TECHNIQUE ON STUDENTS’ SPEAKING ABILITY - Nurdiana; Zelly Putriani; Afrizal; Salsabila Zahra (State Islamic University of Sultan Syarif Kasim Riau, 2026)
This study aimed to determine the effect of using the Talking Stick technique on the speaking ability of the eighth-grade students at SMPN 9 Pekanbaru. The researcher used a quantitative method with a quasi-experimental research design in this study. The population of this study was the eighth-grade students which had the total was 348 students. The researcher used convenience sampling to obtain samples. The sample in this study was 77 students from two classes: 37 students in the experimental class (VIII.5) and 40 students in the control class (VIII.8). In collecting the data, the researcher used an oral test as a pre-test and post-test to determine students' speaking ability. The data analysis technique was the T-test using the SPSS 23 version. The researcher found that sig. (2-tailed) was 0.000. It can be stated that 0.000.